Coatomer complex I is required for the transport of SARS-CoV-2 progeny virions from the endoplasmic reticulum-Golgi intermediate compartment - Ai Hirabayashi; Yukiko Muramoto; Toru Takenaga; Yugo Tsunoda; Mayumi Wakazaki; Mayuko Sato; Yoko Fujita-Fujiharu; Norimichi Nomura; Koji Yamauchi; Chiho Onishi; Masahiro Nakano; Kiminori Toyooka; et al. (mBio)
ABSTRACT SARS-CoV-2 undergoes budding within the lumen of the endoplasmic reticulum-Golgi intermediate compartment (ERGIC), and the progeny virions are delivered to the cell surface via vesicular transport. However, the molecular mechanisms remain poorly understood. Using three-dimensional electron microscopic analysis, such as array tomography and electron tomography, we found that virion-transporting vesicles possessed protein coats on their membrane and demonstrated that the protein coat was coatomer complex I (COPI). During the later stages of SARS-CoV-2 infection, we observed a notable alteration in the distribution of COPI and ERGIC throughout the cytoplasm, suggesting their potential involvement in virus replication. Depletion of COPB2, a key component of COPI, led to the confinement of SARS-CoV-2 progeny virions within the ERGIC at the perinuclear region. While the expression levels of viral proteins within cells were comparable, this depletion significantly reduced the efficiency of virion release, leading to the significant reduction of viral replication. Hence, our findings suggest COPI as a critical player in facilitating the transport of SARS-CoV-2 progeny virions from the ERGIC. Thus, COPI could be a promising target for the development of antivirals against SARS-CoV-2.IMPORTANCESARS-CoV-2 virions are synthesized within the ERGIC and are transported to the cell surface via vesicular transport for release. However, the precise mechanisms remain unclear. Through various electron microscopic techniques, we identified the presence of COPI on virion-transporting vesicles. Alterations in the distribution of COPI and ERGIC in SARS-CoV-2 infected cells are evident, suggesting their involvement in virus replication. When COPB2, a component of COPI, is depleted, progeny virions become trapped within the ERGIC, leading to a reduction in the efficiency of virion release. These findings highlight COPI’s crucial role in mediating SARS-CoV-2 vesicular transport from the ERGIC and suggest it as a potential antiviral target.